Canonical Wnt signaling promotes pacemaker cell specification of cardiac mesodermal cells derived from mouse and human embryonic stem cells. (30th December 2019) - Liang, Wenbin; Han, Pengcheng; Kim, Elizabeth H.; Mak, Jordan; Zhang, Rui; Torrente, Angelo G.; Goldhaber, Joshua I.; Marbán, Eduardo; Cho, Hee Cheol
Abstract: Cardiac differentiation of embryonic stem cells (ESCs) can give rise to de novo chamber cardiomyocytes and nodal pacemaker cells. Compared with our understanding of direct differentiation toward atrial and ventricular myocytes, the mechanisms for nodal pacemaker cell commitment are not well understood. Taking a cue from the prominence of canonical Wnt signaling during cardiac pacemaker tissue development in chick embryos, we asked if modulations of Wnt signaling influence cardiac progenitors to bifurcate to either chamber cardiomyocytes or pacemaker cells. Omitting an exogenous Wnt inhibitor, which is routinely added to maximize cardiac myocyte yield during differentiation of mouse and human ESCs, led to increased yield of spontaneously beating cardiomyocytes with action potential properties similar to those of native sinoatrial node pacemaker cells. The pacemaker phenotype was accompanied by enhanced expression of genes and gene products that mark nodal pacemaker cells such as Hcn4, Tbx18, Tbx3, and Shox2 . Addition of exogenous Wnt3a ligand, which activates canonical Wnt/β-catenin signaling, increased the yield of pacemaker-like myocytes while reducing cTNT-positive pan-cardiac differentiation. Conversely, addition of inhibitors of Wnt/β-catenin signaling led to increased chamber myocyte lineage development at the expense of pacemaker cell specification. The positive impact of canonical Wnt signaling on nodal pacemaker cell differentiation was evidenced in direct differentiation of two human ESC lines and human induced pluripotent stem cells. Our data identify the Wnt/β-catenin pathway as a critical determinant of cardiac myocyte subtype commitment during ESC differentiation: endogenous Wnt signaling favors the pacemaker lineage, whereas its suppression promotes the chamber cardiomyocyte lineage. : Abstract : Canonical Wnt signaling promotes pacemaker cell specification of cardiac mesodermal cells derived from mouse and human embryonic stem cells